Isolation and identification of antioxidant and α-glucosidase inhibitory compounds from fruit juice of Nitraria tangutorum. (15th July 2017) - Zhao, Jian-Qiang; Wang, Yan-Ming; Yang, Yan-Long; Zeng, Ying; Wang, Qi-Lan; Shao, Yun; Mei, Li-Juan; Shi, Yan-Ping; Tao, Yan-Duo
Highlights: The phytochemical research on the fruit juice of Nitraria tangutorum was carried out. Sixteen alkaloids including four new glucose-derived β-carbolines were isolated. Ten non-alkaloids including a new compound were obtained. The biogenetic pathways of1 –8 were proposed. Antioxidant and α -glucosidase inhibitory activities of all isolates were tested. Abstract: Nitraria tangutorum Bor., having edible berries, is valued for reputed health benefits in Qinghai-Tibet plateau. The phytochemical research on the fruit juice of N. tangutorum led to the isolation of twenty-six compounds including five new compounds, tangutorids A–D (1, 2, 3a, and3b ), and (3 E, 5 E )-7- O -β-glucosyl-4-(2-methoxy-2-oxoethyl)hepta-3, 5-dienoic acid (15 ). The structures of these compounds were elucidated through comprehensive spectroscopic analyses. Tangutorids A–F were the first examples of glucose-derived β-carbolines from natural products. The biogenetic pathways of1 –8 were proposed to involve Pictet–Spengler reactions and described starting from the co-isolated tryptophan (10 ) and corresponding aldehydes. All isolates were evaluated for their antioxidant and α -glucosidase inhibitory activities. Compounds21, 22, and24 showed antioxidant activity with SC50 values ranging from 12.2 ± 1.9 to 30.4 ± 2.7 μg/mL, and compound1 showed strong α -glucosidase inhibitory effect with IC50 value of 63.3 ± 4.6 μg/mL.